Memrise: Promoting Students’ Autonomous Learning Skill through Language Learning Application - Dyah Aminatun; Lulud Oktaviani (English Education Study Program, Faculty of Education and Teachers Training, Tidar Univer, 2019)
To master English language, students cannot only learn English from what is learned in the classroom given by the teacher. They need to explore many things to support their understanding about language. Therefore, independent learning skill is crucially needed. The students are the one who knows what they need to study according to their priority. However, sometimes, it is hard for students to build their independent learning skill since there is no encouragement from the teacher to promote it, and also students’ lack of awareness related to what they are learning. The role of technology like online learning application nowadays really helps teachers and students overcome this problem. This study is aimed to explore the use of language learning application named Memrise to enhance students’ autonomous learning skill outside the class, especially in studying English. A descriptive study was conducted to eighteen Management students taking English for Business II subject. The data gained from questioner and interview showed that Memrise helps students learn English and especially improve their vocabulary. Moreover, because it can be accessed anywhere and anytime, students can always learn English whenever they want to. Thus, it really supports students’ independent learning skill and boosts their English skills.